FIRST EDITION - Steppe, Martin (Drug Analytical Research, 2026)
Analysis of drugs requires standing search for reliable analytical techniques, essential to assure their identification and concentration in several matrices. In this context, the edition of scientific works has the objective of contributing with the researchers of the analytical area collaborating with the diffusion and knowledge related to this subject. The editorial team is celebrating the first volume of the journal Drug Analytical Research, a result of the effort of professors and collaborators who have taken up the challenge of expanding the analytical research involving therapeutic substances. The scope of the journal is focused on the analytical determination of drugs in different matrices, impurities, propositions of new analytical methods, as well as the systematic review of issues of separation and quantitative determination. At this moment, we would like to invite to access the website of the journal through the address (http://seer.ufrgs.br/index/php/dar) and appreciate the articles and reviews included in this first edition. Finally, we thank all those who supported this project, especially to Dra. Amanda Thomas Barden, who helped effectively in all stages of publication of this journal. Porto Alegre, August 28th, 2017 Martin Steppe Lead Editor